Chlamydomonas reinhardtii-expressed multimer of ToAMP4 inhibits the growth of bacteria of both Gram-positive and Gram-negative. (April 2020) - Xue, Bin; Dong, Chun-Ming; Hu, He-He; Dong, Bin; Fan, Zhen-Chuan
Graphical abstract: Highlights: The recombinant ToAMP4 was expressed in Chlamydomonas reinhardtii for the first time. The expression of recombinant ToAMP4 was stable. The recombinant ToAMP4 had a broad antibacterial spectrum. The recombinant ToAMP4 had good stability, low hemolysis activity and low cytotoxicity. The recombinant ToAMP4 disrupted bacterial cell morphology and membrane integrity. Abstract: The antimicrobial peptide ToAMP4 was isolated from Taraxacum officinale Wigg. flowers. Bacterial-expressed ToAMP4 showed antifungal activity but was inactive against bacteria. In this study, Chlamydomonas reinhardtii was used to express a C-terminal hemagglutinin (HA) and 6×His double tagged three repeats of ToAMP4 (3×ToAMP4)and the 3×ToAMP4-expressing cells were screened to express 3×ToAMP4 stably following continuous passaging for six months. Finally, a yield of 0.32 % of total soluble protein was achieved for 3×ToAMP4, which inhibits the growth of bacteria of both Gram-positive and Gram-negative at a minimum inhibitory concentration between 40 and 50 μg/ml. C. reinhardtii -derived 3×ToAMP4 maintained high stability in a wide range of temperature and pHs, tolerated to protease digestion at different extents and showed low hemolytic activity and cytotoxicity. Moreover, C. reinhardtii -expressed 3×ToAMP4 effectively caused damage on the membrane of targeted bacterial cells. In conclusion, our data show that C. reinhardtii has the potential to be used as a platform for the production of bioactive ToAMP4.